008.3 Overlapping hiv and sex work stigma: experiences from 14 sites across zimbabwe. (13th September 2015) - Hargreaves, JR; Busza, J; Mushati, P; Fearon, E; Cowan, FM
Abstract : Background: Stigma remains a barrier to female sex workers' (FSW) access to health services, reflecting fears of being identified as engaging in a criminalised and marginalised occupation, and discrimination and mistreatment by health workers. For FSW living with HIV, the additional stigma can exacerbate discrimination and reluctance to seek care. Methods: We describe intersecting patterns of anticipated and experienced stigma related to sex work and HIV status among FSW in Zimbabwe. As part of the baseline survey for the SAPPH-IRe cluster-randomised trial, we recruited 2722 FSW in 14 sites using Respondent Driven Sampling. We asked 9 questions on perceived sex-work-related stigma. Women self-identifying as HIV+ (n = 1011) answered an additional stigma scale. Results: Sex work-related stigma was higher than HIV-related stigma. This held true for internalised, perceived and experienced forms. For instance, 37% of FSW reported "feeling ashamed" due to their occupation, compared to 20% of those with HIV feeling shame due to their status; 59% of FSW felt they had "lost respect or standing" as a result of being sex workers, while 23% among the HIV+ felt HIV had reduced their social status. In relation to being "talked about badly" for being FSW or HIV+, the figures were 47% and 12%. Similarly, 19% of respondents reported being insulted as FSW but just 5% of those living with HIV felt insulted due to their status. Denial of services by health care workers was low, but nonetheless considered higher for being a sex worker compared to being HIV+. Conclusions: Sex workers in Zimbabwe have high HIV prevalence and experience layered stigma for their role as "immoral" women as well as "vectors of disease." That sex-work related stigma is more pervasive than HIV-related stigma may be due to "normalisation" of HIV following introduction of widespread treatment, with comparatively greater disapproval for sex work. Disclosure of interest statement: The SAPPH-IRe trial is using Truvada donated by Gilead. We have no other relationships with commercial entities to disclose.